2014
DOI: 10.3390/bioengineering1040260
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Filtration Processes—Microfiltration and Depth Filtration for Harvest of a Therapeutic Protein Expressed in Pichia pastoris at Constant Pressure

Abstract: Filtration steps are ubiquitous in biotech processes due to the simplicity of operation, ease of scalability and the myriad of operations that they can be used for. Microfiltration, depth filtration, ultrafiltration and diafiltration are some of the most commonly used biotech unit operations. For clean feed streams, when fouling is minimal, scaling of these unit operations is performed linearly based on the filter area per unit volume of feed stream. However, for cases when considerable fouling occurs, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…The models described in Table 4 do provide a common framework that is extensively deployed within membrane filtration [33,55,[124][125][126][127][128][129]. The models were originally intended for dead-end filtration and did not consider flux recovery methods.…”
Section: Structurementioning
confidence: 99%
“…The models described in Table 4 do provide a common framework that is extensively deployed within membrane filtration [33,55,[124][125][126][127][128][129]. The models were originally intended for dead-end filtration and did not consider flux recovery methods.…”
Section: Structurementioning
confidence: 99%
“…These models were originally developed for frontal filtration at constant pressure [6][7][8][9]. However, it has been demonstrated that, under specific conditions, Hermia models could be applied in tangential filtration [10][11][12][13][14][15][16][17][18][19][20][21]. Hong et al [22] showed during tangential filtration of colloidal suspensions that the filtration process before the "pseudo stationary state" is similar to the frontal filtration.…”
Section: Introductionmentioning
confidence: 99%
“…The intermediate blocking model is used when particles smaller than the pore size enter the pores and get either adsorbed or deposited onto the pore walls. And when particles get accumulated inside the membrane on the pore walls and the resulting constrictions of pores reduce the membrane's permeability the standard blocking model can be used [FIELD 2010;SAMPATH et al 2014]. These mechanisms have been used individually as well as in combination to explain experimental various observations [HALE, DANIELS 1961;HO, ZYDNEY 2000;SAMPATH et al 2014].…”
Section: Introductionmentioning
confidence: 99%